202 Impact of Urinary Incontinence on Sexual Function in Patients Presenting for Lower Urinary Tract Symptoms. (1st May 2022) - Fallara, G.; Boeri, L.; Candela, L.; Costa, A.; Capogrosso, P.; Cazzaniga, W.; Schifano, N.; Pozzi, E.; Belladelli, F.; Cignoli, D.; Colandrea, G.; Cornelius, J.; et al.
ABSTRACT: Introduction: Patients with low urinary tract symptoms (LUTS) frequently complain some sexual dysfunction and sometimes even episodes of bothersome urinary incontinence (UI). Objective: We aimed to assess the relationship between UI (as measured with the ICIQ-UI-SF), and sexual disfunction (as measured with the IIEF), in men presenting with LUTS at a tertiary-referral centre. Methods: In this cross-sectional study, data were retrospectively retrieved from 938 consecutive patients aged >18 years seeking first medical help for self-reported LUTS (i.e., all patients had IPSS≥1). All patients had a complete clinical assessment and completed the IPSS, the ICIQ-UI-SF, the OAB-q and the IIEF questionnaires. Patients were stratified into "no UI" (ICIQ-UI-SF=0), "mild UI" (ICIQ-UI-SF=1-7), "moderate UI" (ICIQ-UI-SF=8-13) or "severe UI" (ICIQ-UI-SF=14-21). ANOVA test assessed differences in baseline characteristics among these groups. Spearman correlation test was applied to evaluate the correlation between ICIQ-UI-SF and IIEF domain scores. A linear regression analyses tested putative risk factors associated with increased ICIQ-UI-SF scores. Result: Of 938, 589 (63%) patients had no UI, 237 (25%) had mild UI, 76 (8%) moderate UI and 36 (4%) severe UI. There were no substantial differences in total PSA levels and uroflowmetry parameters among UI groups, whereas prostate volume, IPSS and OAB-q scores were higher as UI symptoms increased (all p≤ 0.03). A negative correlation was found between IIEF-total, IIEF-Erectile Function, IIEF-Intercourse Satisfaction and IIEF-Overall Satisfaction scores and ICIQ-UI-SF scores (i.e., the worse UI symptoms, the worse the overall sexual function (rho= -0.12; p<0.001), IIEF-EF (rho= -0.15; p<0.001), IIEF-IS (rho = -0.1; p=0.004) and IIEF-OS (rho = -0.12; p<0.001). Sexual desire and orgasmic function domains were not correlated with ICIQ-UI-SF. Finally, higher BMI (Coeff 0.12; 95% CI 0.03-0.32; p=0.011), diabetes (Coeff 1.76; 0.35-3.18; p=0.015) and presence of comorbidities (Coeff: 0.9; 0.06-0.1.74; p=0.035) were associated with higher ICIQ-UI-SF scores. Main limitations of the study were that ICIQ-UI-SF does not discriminate between urge or stress UI. Conclusion: In patients presenting with LUTS, the presence of urinary incontinence was associated with worsening of overall sexual function (i.e., erectile function, intercourse satisfaction and overall satisfaction). Disclosure: Work supported by industry: no.